MENINGKATKAN PRESTASI KERJA PEGAWAI NEGERI SIPIL PEMERINTAH PROVINSI KALIMANTAN SELATAN MELALUI PENDIDIKAN DAN PELATIHAN (DIKLAT): STUDI PADA PESERTA DIKLAT PIM IV PADA BADAN PENDIDIKAN DAN PELATIHAN DAERAH PROVINSI KALIMANTAN SELATAN - Fathul Jannah; Misransyah Akos (Administraus, 2019)
This study aims to determine, examine and analyze the influence of Education and Training on the work achievements of Training Participants in the Education and Training Agency of the Province of South Kalimantan. The method used in this study is Quantitative Descriptive by using two approaches, namely: (1) descriptive statistical test that is to know the tendency or frequency distribution of the respondent's answer to the questionnaire proposed primarily to know the mean of each item / proposed indicators, (2) influence test between X and Y variables proposed in the research. This research uses explanatory research design approach. The results showed that the Education and Training Employees have a partial influence on Employee Performance is indicated by t arithmetic > t table is 4.650> 1.999 or sig t value (0,000) < Î± = 0.05 then Employee Training has a significant influence on employee performance. Thus, the test shows H0 rejected and H1 accepted. From table 4 it is known that there is a contribution between Education and Training on Civil Servant Employment Performance of South Kalimantan Provincial Government of 29.2%, while the rest of 70.8% is caused by other variables not included in this research. The Variables of Training have a significant influence on the performance of Civil Servant of South Kalimantan Provincial Government following Diklat PIM IV for 2016.